2018
DOI: 10.2147/ijn.s167670
|View full text |Cite
|
Sign up to set email alerts
|

Mangosteen pericarp extract embedded in electrospun PVP nanofiber mats: physicochemical properties and release mechanism of α-mangostin

Abstract: Backgroundα-Mangostin is a major active compound of mangosteen (Garcinia mangostana L.) pericarp extract (MPE) that has potent antioxidant activity. Unfortunately, its poor aqueous solubility limits its therapeutic application. Purpose: This paper reports a promising approach to improve the clinical use of this substance through electrospinning technique.MethodsPolyvinylpyrrolidone (PVP) was explored as a hydrophilic matrix to carry α-mangostin in MPE. Physicochemical properties of MPE:PVP nanofibers with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 78 publications
5
55
0
Order By: Relevance
“…The nanomicelle uptake was mediated by endocytosis, a finding that indicated intracellular delivery of α-mangostin that could be associated with potential cytotoxicity (IC 50 of 8.9 ± 0.2 μg/mL). 82 Chitosan, PLGA Colloidal extraction solvent evaporation [75] PEG, PLA Emulsion/solvent evaporation techniques [76] PLGA Double emulsion solvent evaporation method [42] EC-MC Spray drying [77] Chitosan, alginate and genipin Ionotropic gelation method [78] β-cyclodextrin Inclusion complex technique [79] β-cyclodextrin-chitosan Inclusion complex [80] β-cyclodextrin Inclusion complex [81] Nanomicelles PVP Solvent evaporation method [82] MPEG and PLA Single-step self-assembly method [83] MPEG and PCL Self-assembly method [84] Liposome nanoparticles Transferrin Thin film hydration [85] Soya lecithin Phase separation coacervation method [86] Cholesterol, Tween 60 and ethanol Film hydration method [87] Solid lipid nanoparticles Lavender essential oil and cetyl palmitate Hot and high-pressure homogenisation techniques [88] PLGA and CD44 thioaptamer Nanoprecipitation combined with self-assembly [89] Nanofibres Thiolated chitosan Electrospinning [90] PVP Electrospinning [91] Metal nanoparticles Ag (silver) Chemical reaction by using silver nitrate (AgNO3) [92] Gold, PEI, cyclodextrin and tanshinone Chemical reaction using polyethyleneimine (PEI) [93] Emulsion nanoparticle Captex 200 P, Tween 80, carbopol 90 and silica Solid self-emulsification [94] Oleic acid, isopropyl myristate, Cremophor EL, Tween 80, carboxymethylcellulose sodium Self-microemulsion [31] In another study, α-mangostin nanomicelles with methoxypoly(ethylene glycol)-poly(lactide) (MPEG-PLA) were developed by a single-step self-assembly method for malignant glioma. In vitro and in vivo assays showed that the α-mangostin/MPEG-PLA nanoparticles inhibited cell growth and induced apoptosis-with cleaved caspase expression, DNA fragmentation, downregulation of antiapoptotic molecules and up-regulation of apoptotic molecules.…”
Section: Nanomicellesmentioning
confidence: 99%
“…The nanomicelle uptake was mediated by endocytosis, a finding that indicated intracellular delivery of α-mangostin that could be associated with potential cytotoxicity (IC 50 of 8.9 ± 0.2 μg/mL). 82 Chitosan, PLGA Colloidal extraction solvent evaporation [75] PEG, PLA Emulsion/solvent evaporation techniques [76] PLGA Double emulsion solvent evaporation method [42] EC-MC Spray drying [77] Chitosan, alginate and genipin Ionotropic gelation method [78] β-cyclodextrin Inclusion complex technique [79] β-cyclodextrin-chitosan Inclusion complex [80] β-cyclodextrin Inclusion complex [81] Nanomicelles PVP Solvent evaporation method [82] MPEG and PLA Single-step self-assembly method [83] MPEG and PCL Self-assembly method [84] Liposome nanoparticles Transferrin Thin film hydration [85] Soya lecithin Phase separation coacervation method [86] Cholesterol, Tween 60 and ethanol Film hydration method [87] Solid lipid nanoparticles Lavender essential oil and cetyl palmitate Hot and high-pressure homogenisation techniques [88] PLGA and CD44 thioaptamer Nanoprecipitation combined with self-assembly [89] Nanofibres Thiolated chitosan Electrospinning [90] PVP Electrospinning [91] Metal nanoparticles Ag (silver) Chemical reaction by using silver nitrate (AgNO3) [92] Gold, PEI, cyclodextrin and tanshinone Chemical reaction using polyethyleneimine (PEI) [93] Emulsion nanoparticle Captex 200 P, Tween 80, carbopol 90 and silica Solid self-emulsification [94] Oleic acid, isopropyl myristate, Cremophor EL, Tween 80, carboxymethylcellulose sodium Self-microemulsion [31] In another study, α-mangostin nanomicelles with methoxypoly(ethylene glycol)-poly(lactide) (MPEG-PLA) were developed by a single-step self-assembly method for malignant glioma. In vitro and in vivo assays showed that the α-mangostin/MPEG-PLA nanoparticles inhibited cell growth and induced apoptosis-with cleaved caspase expression, DNA fragmentation, downregulation of antiapoptotic molecules and up-regulation of apoptotic molecules.…”
Section: Nanomicellesmentioning
confidence: 99%
“…3A and B. Generally, the high intensity and sharpness of the peak indicate a crystalline nature [15,16] . The AM showed intense peak at diffraction angle of 2-theta at 12 from the broad peak with low intensity at 16.81 and 29.68° (2-theta).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Therefore, the partial crystalline of AM was observed in AM-FFG2 film. In addition, the amorphous nature of AM in the film could be a result from the molecular interaction between AM and film-forming polymer via hydrogen bond which associated with reduced molecular mobility and consequently reduced drug recrystallization [15] .…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The U.S. Food and Drug Administration has approved PVP for a wide variety of applications and it is generally considered safe. Meanwhile, because of its well spinnable and mechanical properties, PVP can be used alone or combined with other polymers to fabricate electrospinning fibers containing drugs, such as mangostin-loaded PVP nanofibers [31] and naproxen-loaded PVP-ethyl cellulose nanofibers [32]. Cellulose acetate (CA, Figure 1C), an acetate ester derivative of cellulose, possesses advantageous properties in biodegradability, biocompatibility, insolubility in water, and nontoxicity [33], and is also widely used to fabricate drug-loaded electrospinning fibers, such as ibuprofen-loaded nanofibers [34], and nisin-loaded nanofibers [35].…”
Section: Sample Preparationmentioning
confidence: 99%